Meaning The Various Forms Of BeliefIn Past And Modern Society. - Diputra, Gede Bagus Wira; Arta, Putu Eddy Purnomo (Socious Journal, 2025)
In the principle of trust there are two underlying elements, namely humans as believers and those they believe in. Rites in community traditions have noble value for the survival of mankind. If humans can understand it properly, then these values ​​will manifest character traits, so that it can become the basis for the growth of wisdom. In the history of human belief that goes back thousands of years, only a few recorded developments in belief systems in the supernatural, namely dynamism, animism, polytheism, henotheism and monotheism. Beliefs in dynamism and animism are beliefs that are considered to be the beginning of human beliefs, Until now, this belief is still embedded in various levels of society. Although that belief is not like primitive society, however, the phenomena and practices are still similar. Therefore, this research will discuss the meaning of each type of belief. This research is classified as qualitative research, The method used is literature study by utilizing various library references in the form of books and scientific articles then carry out analysis, think critically-scientifically, and attempt to carry out theorization based on the variables that have been observed.